2019
DOI: 10.1074/mcp.ra119.001446
|View full text |Cite
|
Sign up to set email alerts
|

Systems-level Analysis Reveals Multiple Modulators of Epithelial-mesenchymal Transition and Identifies DNAJB4 and CD81 as Novel Metastasis Inducers in Breast Cancer

Abstract: Epithelial-mesenchymal transition (EMT) is driven by complex signaling events that induce dramatic biochemical and morphological changes whereby epithelial cells are converted into cancer cells. However, the underlying molecular mechanisms remain elusive. Here, we used mass spectrometry based quantitative proteomics approach to systematically analyze the post-translational biochemical changes that drive differentiation of human mammary epithelial (HMLE) cells into mesenchymal. We identified 314 proteins out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…Megenta points, which are malignancy associated EMT factors (Fig. 4A) that are altered by SNAI1/TWIST1 overexpression (51)(52)(53)(54), were also identified as being altered following the induction of RPE-EMT.…”
Section: Integrated Transcriptomic and Proteomic Analysis Of Hrpe-emtmentioning
confidence: 92%
“…Megenta points, which are malignancy associated EMT factors (Fig. 4A) that are altered by SNAI1/TWIST1 overexpression (51)(52)(53)(54), were also identified as being altered following the induction of RPE-EMT.…”
Section: Integrated Transcriptomic and Proteomic Analysis Of Hrpe-emtmentioning
confidence: 92%
“…Reaction was quenched with acidification and the resulting peptides were desalted [ 37 ] and then analyzed with reversed-phase nLC (NanoLC-II, Thermo Scientific) combined with orbitrap mass spectrometer (Q Exactive Orbitrap, Thermo Scientific). The raw files were processed with Proteome Discoverer 1.4 (Thermo Scientific) using human Uniprot database (Release 2015–21,039 entries) as previously described [ 36 , 38 ]. Two technical replicates were performed for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The recent proteomic investigations identified another member of the HSP40 subfamily, DnaJB4, as a new driver of EMT in breast cancer [132]. The same researchers showed that the suppression of DnaJB4 in breast cancer cells with a mesenchymal phenotype impaired their migration capacity in vitro and reduced both primary tumor growth and lung metastasis occurrence in vivo.…”
Section: Hsp40mentioning
confidence: 99%